Struktur Histologi Otot Femur Kelinci (Lepus Sp.) Setelah Perlakuan Implantasi Material Stainless Steel Aisi 316l Selama 2,5 Bulan - Primadiani, Isabella Vanny; Mardiati, Siti Muflichatun; Tana, Silvana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Production implant orthopedic domestic with 316L Stainless steel base material which use the material dimensions of the Indonesian non-import until now hasnâ€™t been researched. Research the effect of implantation of these materials to health conditions need to be conducted on animal models, such as the rabbit before it wad applied to humans. This study aims to determine the histological changes in the femoral muscle of rabbits after implantation of AISI 316L stainless steel for 2.5 months, as part of the basic data for further research in order to figure out orthopedic implants that can be used by the body. This study compared the P0: rabbit was not given implantation of stainless steel AISI 316L with P1: Rabbits were given treatment AISI 316L stainless steel implants in the quadriceps femoris muscle parallel to the femur bone. Implantation of the implant material was conducted for 2.5 months. Histological changes observed were the presence or absence of necrosis, fibrosis and tissue cavities in the rabbit femoral muscle tissue. The results showed there were no three variables were observed. It is concluded AISI 316L stainless steel did not cause structural changes in muscle histology in a rabbit femur after implantation for 2.5 months; so that these materials can be used as an implant material in the body. Â Keywords: rabbit, stainless steel AISI 316L, histology, muscle